Cutting edge: selective requirement for the Wiskott-Aldrich syndrome protein in cytokine, but not chemokine, secretion by CD4+ T cells - Morales-Tirado, Vanessa; Johannson, Sara; Hanson, Elaine; Howell, Alan; Zhang, Jinyi; Siminovitch, Katherine A; Fowell, Deborah J (The Journal of immunology (1950), 2004)
The mechanism of cytokine secretion is not well understood, but cytokines appear to be synthesized and released in a polarized fashion toward an Ag-specific target cell. In this study, we demonstrate that the Wiskott-Aldrich syndrome protein (WASp) is an essential component of the cytokine secretory pathway in CD4(+) T cells. Murine WASp-deficient CD4(+) T cells fail to polarize cytokines toward a target and show an unexpected and striking block in cytokine secretion. In contrast, chemokine secretion and trafficking of plasma membrane proteins, transported via the constitutive secretory pathway, are unaffected by the lack of WASp. These results suggest that CD4(+) T cell cytokines require a specialized, WASp-dependent pathway for cellular traffic and/or vesicle release that is distinct from that required for chemokine release. We propose that the use of different secretory pathways for cytokines and chemokines enables CD4(+) T cell activity to be further fine-tuned to serve specialized effector functions.